2010
DOI: 10.1002/tea.20358
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a classroom intervention on grade 10 students' argumentation skills, informal reasoning, and conceptual understanding of science

Abstract: The literature provides confounding information with regard to questions about whether students in high school can engage in meaningful argumentation about socio‐scientific issues and whether this process improves their conceptual understanding of science. The purpose of this research was to explore the impact of classroom‐based argumentation on high school students' argumentation skills, informal reasoning, and conceptual understanding of genetics. The research was conducted as a case study in one school with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
176
2
20

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(222 citation statements)
references
References 46 publications
9
176
2
20
Order By: Relevance
“…In addition, assuming there is a relationship between knowledge and behavior (Yencken et al 2000), we can investigate if opinion can be influenced through increased knowledge. Many studies have been undertaken in formal learning environments to assess background knowledge of climate change prior to instruction (Andersson and Wallin 2000;Boyes et al 2004) and post-instruction (Rye et al 1997;Venville and Dawson 2010). Both groups of studies (students and general public) investigate opinion and perceptions of climate change but few have addressed the relationship between scientific understanding of climate science and the individual opinion/belief system and whether climate science understanding can be improved from pre-instruction to postinstruction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, assuming there is a relationship between knowledge and behavior (Yencken et al 2000), we can investigate if opinion can be influenced through increased knowledge. Many studies have been undertaken in formal learning environments to assess background knowledge of climate change prior to instruction (Andersson and Wallin 2000;Boyes et al 2004) and post-instruction (Rye et al 1997;Venville and Dawson 2010). Both groups of studies (students and general public) investigate opinion and perceptions of climate change but few have addressed the relationship between scientific understanding of climate science and the individual opinion/belief system and whether climate science understanding can be improved from pre-instruction to postinstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Several connections have been empirically drawn between socio-scientific issues and other important aspects of science education including argumentation (39,32,45), informal reasoning (46,51), and the acquisition of content knowledge (35,43). Understanding science content as well as engaging in informal reasoning and argumentation is considered as fundamental to the negotiation and resolution of SSI.…”
Section: Introductionmentioning
confidence: 99%
“…Student learning and development in the areas of understanding science and scientific knowledge, argumentation, reasoning and decision-making are expected outcomes needed for young people to engage in public discussions influenced by the processes and products of modern technology (10,20,31,48). This perspective suggests that the implementation of SSIs in the science classrooms can not only be productive (14,32,36), but should also be an integral part of today's science training (10,41,45,48).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the study reported in Mercer et al (2004) suggest that exploratory talk, or the discursive practice in which students express and collaboratively explore their opinions through a systematic and joint reasoning, has an impact on secondary students' science learning and reasoning skills. In addition, results from four studies with primary (Che & She, 2012) and secondary students (Venville & Dawson, 2010;Wilson et al, 2010;Zohar & Nemet, 2002) support this conclusion. However, there are uncertainties about how these results should be interpreted.…”
Section: Argumentation For Science Learningmentioning
confidence: 87%
“…Although there is scarce research testing these benefits, some empirical evidence on peer interactions partially supports it (Asterhan & Schwarz, 2007Howe et al, 2007). Some studies have tested the effect of the argumentative type of whole-class talk on learning, but they are only partially conclusive and do not prove the effect of the discussion of contradictory ideas (Che & She, 2012;Mercer, Dawes, Wegerif, & Sams, 2004;Venville & Dawson, 2010;Wilson, Taylor, Kowalski, & Carlson, 2010;Zohar & Nemet, 2002). Considering that whole-class interactions are the most frequent ones in classrooms around the world (Howe, 2010), it is relevant to investigate the effect of whole-class discussion on learning.…”
mentioning
confidence: 99%